DIGITAL MARKETING COMMUNICATION: A CASE STUDY OF COVID-19 PURCHASING DECISION RELATED TO SOCIAL MEDIA AND E-WOM - Sri Murtiasih; Erny Pratiwi; Masodah Masodah; Purnawarman Musa (Jurnal Ilmiah Ekonomi Bisnis, 2023)
The COVID-19 pandemic that occurred all across the globe affected the economy. The firm is responsible for promotions, and clients use different types of technology to make purchases. Digital marketing employs social media to promote a product using electronic communication tools, which assist customers in making better-educated buying choices and persuade them to purchase a product or service. This study used purposeful sampling to acquire data, and the sample size was computed using answers from 441 participants who completed online surveys. Participants must be at least 20 years old and active purchasers in the retail internet industry. The suggestion indicates that customers may obtain a product or service via social media or e-WOM. Our SEM-based analysis revealed conformity with the value CFI is 0.954, the value RFI is 0.918, the value NFI is 0.931, and the value RMSEA is 0.066.  Consequently, advertising using digital marketing on social media during the COVID-19 epidemic has substantially influenced consumers' purchasing decisions.